A Triple Band Bow Tie Array Antenna Using Both-sided MIC Technology - Akimun Jannat Alvina; Samia Sabrin; Mohammad Istiaque Reja; Jobaida Akhtar (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A single-fed linearly polarized 2x2 microstrip bow tie array antenna is proposed. The feed network has microstrip line and slot line where microstrip-slot branch circuit is connected in parallel. The feed network of the array is designed using both-sided MIC Technology to overcome the impedance matching problem of conventional feed networks. The 2x2 half bow tie array antenna is also truncated with spur lines for optimization of antenna performance. The array antenna unit can be realized in very simple and compact structure, as all the antenna elements and the feeding circuit is arranged on a Teflon glass fiber substrate without requiring any external network. The design frequency of the proposed antenna is 5 to 8 GHz (CBand) and the obtained peak gain is 12.41 dBi. The resultant axial ratio indicates that linear polarization is achieved.